POSSIBLE WAYS OF RAISING EFFICIENCY OF UNIVERSITY PUBLISHING ACTIVITY - Kirill S. Zintsov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with publishing of teaching and methodological literature in university. The author analyzed the dynamics of books and brochures publishing on target purpose in 2013-2015 in typographical units and circulation. Major problems of publishing activity in higher school were identified, they are connected mainly with general books market trends and shaping the educational environment. The author touched upon the aspect of necessary participation of university publishing houses in forming professional competences and in upbringing of young people. By analyzing book-supply to the teaching process and classification of text-books the article puts forward the key lines in improving publishing activity in university.